2006
DOI: 10.1200/jco.2006.24.18_suppl.571
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of sequence vs. combination of capecitabine (X) and docetaxel (T): XT vs. T followed by X after progression as first-line therapy for patients (pts) with metastatic breast cancer (MBC)

Abstract: 571 Background: Capecitabine (Xeloda [X]) and docetaxel (Taxotere [T]) are highly active single agents in MBC. The XT combination leads to superior overall survival (OS), time to progression (TTP) and response rate (RR) vs. T alone in anthracycline-preatreated MBC [O’Shaughnessy et al. J Clin Oncol 2002], although only one third of pts in the T group received X after progression. We designed this study to determine whether XT is better than sequential T→X in first-line MBC. Methods: 100 pts with measurable MB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Eight other small phase II or phase III studies comparing sequential versus combination approaches showed different results. Two (15,16) showed a better response rate in the combination arm, whereas others showed similar efficacy of both approaches (17)(18)(19)(20)(21)(22). Safety profile was better in the sequential arm in three of these eight trials (17)(18)(19), whereas two trials showed similar toxicity (15,20) and in three hematological toxicity was higher in the sequential arm (16,21,22).…”
Section: Discussionmentioning
confidence: 95%
“…Eight other small phase II or phase III studies comparing sequential versus combination approaches showed different results. Two (15,16) showed a better response rate in the combination arm, whereas others showed similar efficacy of both approaches (17)(18)(19)(20)(21)(22). Safety profile was better in the sequential arm in three of these eight trials (17)(18)(19), whereas two trials showed similar toxicity (15,20) and in three hematological toxicity was higher in the sequential arm (16,21,22).…”
Section: Discussionmentioning
confidence: 95%
“…To further study the question of combination versus sequential therapy, Beslija et al conducted a trial with 100 patients who had received prior adjuvant anthacyclines, but no prior chemotherapy for metastatic breast cancer. 27 Patients were randomized to capecitabine and docetaxel, at a reduced dose of docetaxel compared to the O'Shaughnessy trial, 13 or to full-dose docetaxel fol-lowed by capecitabine on progression. The response rates, time to progression and overall survival were superior in the combination arm, (RR 68 vs. 40%, P = 0.004; median TTP 9.3 vs. 7.7 months, P = 0.001; median OS 22 vs. 19 months, P = 0.006).…”
Section: Docetaxel Combinationsmentioning
confidence: 99%
“…In two other trials using a combination of capecitabine and taxanes with a similar design but differences in type of trial, doses and order of sequence of the two drugs, and taxane used [140,141], a higher ORR was reported, but this translated into a longer TTP and OS only in one trial [141]. Two phase II trials [142,143] and three phase II randomized trials [137][138][139] have compared combination chemotherapy with planned sequential therapy, with no significant differences in activity and efficacy but a better safety profile with sequential therapy in the majority of trials.…”
Section: Combination Versus Sequential Ctmentioning
confidence: 99%